Access to and Control over Household Resources: A Consistency Check Using Gender Analysis and Household Survey Data - Devkota, D (Nepal Agriculture Research Journal, 2009)
A study was conducted during 1998 covering three Village Development Committees (VDCs) of Chitwan district, Nepal, to examine the consistency of results if carried out independently using formal and informal methods of information collection. Gender analysis (access and control profiles), and a face-to-face household survey (n = 123 households) were employed for this purpose. Gender differences in access to and control over household resources was studied. Results showed a consistent response from both household survey and gender analysis for most of the parameters studied, such as access to agriculture extension and veterinary services, participation in training, and community work. Gender response for control over resources, such as income from small animals was also similar from both methods. However, some of the parameters were not consistent in response. For example, there was no participation of women in control over income from cash crops and cereal crops and large animals as strongly indicated by gender analysis, which was not visible in the case of household survey. This raises a question about the reliability of using only one approach of information collection for rural development research. On the basis of these results, we suggest a combine approach of quantitative and qualitative methods of data collection, which could be more reliable, informative and appropriate. The use of multiple methods also allows the researcher to cross-reference in order to validate the trustworthiness of information. Key words: Gender analysis; household survey; triangulation DOI: 10.3126/narj.v7i0.1875 Nepal Agriculture Research Journal Vol.7 2006 pp.98-102